Total Sky Imager observations during POLARSTERN cruise PS127, Bremerhaven - Cape Town - Rico Hengst; Kevin Ohneiser; Majid Hajipour; Jonas Witthuhn; Ronny Engelmann (PANGAEA, 2022)
The dataset consist of camera shots of the sky. The camera - a total sky imager manufactured by Vivotek - was mounted at the top of the Research Vessel Polarstern. On the Atlantic transit from Bremerhaven to Cape Town in December 2021 this camera shots were taken with a temporal resolution of 15 seconds. The dataset represents the visible projection of weather conditions and cloud cover recorded on the vessel Polarstern in the direction near the zenith. These observations are useful for the interpretation of the atmospheric radiation measurements.